P631 Long-term safety of vedolizumab versus other biologic agents in ulcerative colitis (UC) and Crohn's Disease (CD): Results from a large multinational prospective observational study. (30th January 2023) - Louis, E; Sebastien, S; Siegmund, B; Bossuyt, P; Danese, S; de Boer, N; Loftus, E; Moum, B; Peyrin-Biroulet, L; Schreiber, S; Zhou, J; Wernicke, J; et al.
Abstract: Background: Vedolizumab (VDZ) is a gut-selective humanised monoclonal anti-α4β7 integrin antibody for treatment of UC and CD. This post-authorization safety study (PASS) compared long-term safety in patients (pts) treated with VDZ or other biologics for UC or CD. Methods: This was a prospective, observational, multicentre, cohort study in pts with UC or CD starting treatment with VDZ or other biologics (NCT02674308, EUPAS6469). Pts were biologic naïve (VDZ=35%, Other biologic=65%) or had prior exposure to biologics other than VDZ and were followed for up to 7 yrs. Pts were treated under usual standard of care as directed by their physician with no discontinuation from the study due to physician-directed treatment changes. The primary safety outcome was serious infections and was compared between cohorts using a Cox proportional hazards model adjusted by propensity score (with other biologics as reference). Secondary safety outcomes were adverse events (AE) of special interest (AESI) as listed in Tables 2 and 3. Results: In total, 5208 patients were enrolled across 21 countries between Mar 2015 and Jul 2019. The full analysis set comprised 5008 pts (VDZ=2502; other biologic=2506) and mean (SD) study duration was 37.4 (14.1) months. Consistent with the observational nature of the study and the current standard of care, the baseline characteristics in the two cohorts were imbalanced (Table 1). The overall treatment-emergent Adverse Event (AE) rate was 61.3% (VDZ) and 59.5% (other biologic), with serious AEs in 27.5% (VDZ) and 25.7% (other biologic), respectively. In UC pts, the incidence rate (IR) of serious infections were: 0.014 (95% CI: 0.010, 0.019) [VDZ] and 0.015 (0.010, 0.023) [other biologic], with a hazard ratio (HR) of 1.018 (0.931, 1.114), p=0.70 (Table 2). In CD pts, corresponding findings were 0.012 (95% CI: 0.008, 0.017) [VDZ] and 0.006 (95% CI: 0.004, 0.009) [other biologic] with HR of 1.035 (0.959, 1.117), p=0.38 (Table 3). The incidence of primary and secondary safety outcomes is reported in Table 2 for UC and Table 3 for CD. There were no safety issues relating to pregnancy and no cases of PML observed. There were 19 deaths in the VDZ cohort (1 case of pneumonia deemed as treatment-related); and 13 deaths in the other biologic cohort, 2 cases deemed treatment-related (one case septic shock and pneumonia; one case non-small cell lung cancer). Clinical outcomes and quality of life (QoL) measures were comparable between cohorts. Conclusion: In this long-term, prospective, real-world observational study of a large multinational population under routine standard of care there was no new safety signal identified in relation to VDZ. Results are consistent with the known safety profile of VDZ.